Sultan Pahang’s brother conferred with UMP Lifelong Professional Learning Award - Shalfarina, Shahriman (2018)
Despite being a busy businessman and serving as Commanding Oicer of the First Battalion 505 Territorial Army Regiment, it did not stop Lieutenant Colonel Tengku Dato’ Sri Kamarulzaman Al-Haj Ibni AlMarhum Sultan Sir Abu Bakar from continuing to pursue an Executive Masters’ Degree in Project Management in Universiti Malaysia Pahang (UMP).